(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
Muslims, especially students, are often prohibited from wearing turbans in schools as well as while riding motorcycles, whereas Sikh followers are given leeway to wear turbans at all times and occasions. This situation suggests that there exists discrimination in law enforcement, even though the law guarantees equality for all religions in Malaysia. This article aims to determine whether there exists racial discrimination with regard to the wearing of turbans by Muslims and Sikhs in Malaysia. The finding shows that the special exception given to the Sikhs is to foster racial understanding and to protect their right, whereby wearing if the turban is compulsory, while for Muslims it is merely encouraged. Keywords: turban, Islam, Sikhism, discrimination, International Convention on the Elimination of All Forms of Racial Discrimination (ICERD) 1969